ANEMIA PLUS HYPOPROTEINEMIA IN DOGS : VARIOUS PROTEINS IN DIET SHOW VARIOUS PATTERNS IN BLOOD PROTEIN PRODUCTION BEEF MUSCLE, EGG, LACTALBUMIN, FIBRIN, VISCERA, AND SUPPLEMENTS - Whipple, G. H. (The Rockefeller University Press, 1951)
Dogs with sustained anemia plus hypoproteinemia due to bleeding and a continuing low protein or protein-free diet containing abundant iron have been used in the present work to test food proteins and supplements as to their See PDF for Structure capacity to produce new hemoglobin and plasma proteins. The reserve stores of blood protein-producing materials are thus largely depleted in such animals and sustained levels of 6 to 8 gm. per cent hemoglobin and 4 to 5 gm. per cent plasma protein can be maintained for considerable periods of time. The stimulus of double depletion drives the body to use all protein building materials with the utmost conservation. This represents a severe biological test for food and body proteins and its assay value must have significance. Measured by this biological test in these experiments, casein stands well up among the best food proteins. The ratio of plasma protein to hemoglobin is about 40 to 50 per cent, which emphasizes the fact that these dogs produce on most diets about 2 gm. hemoglobin to 1 gm. plasma protein. The reason for this preference for hemoglobin production is obscure. The mass of circulating hemoglobin is greater even in this degree of anemia and the life cycle of hemoglobin is much longer than that of the plasma protein. Egg protein, egg albumin, and lactalbumin all favor the production of more plasma protein and less hemoglobin as compared with casein. The plasma protein to hemoglobin ratio is increased, sometimes above 100 per cent. Supplements to the above proteins of casein digests or several amino acids may return the response toward that which is standard for casein. Histidine as a supplement to egg protein increases the total blood protein output and brings the ratio of plasma protein to hemoglobin toward that of casein. Beef muscle goes to the other extreme and favors new hemoglobin production up to 4 gm. hemoglobin to 1 gm. plasma protein—a ratio of 25 per cent. The total amounts of new blood proteins are high. Lactalbumin as compared with casein shows a lower total blood protein output and a plasma protein to hemoglobin ratio of 70 to 90 per cent. Amino acid supplements are less effective. See PDF for Structure Fibrin is a good food protein in these experiments—much like casein. When fed over these 5 week periods it causes a sustained increase in blood fibrinogen. Folic acid in the doses given has no effect on the expected response to various diets. Peanut flour is a very poor diet for the production of new hemoglobin and plasma proteins. Small supplements of casein and beef show a significant response with improved output of blood proteins. Soy bean flour gives a poor response and wheat gluten a good response with adequate output of blood proteins. Visceral products show some variety. Beef heart is not as effective as beef muscle. Beef spleen, kidney, and pancreas give good responses but not up to casein. Pig stomach, beef brain, and calf thymus are below average. The plasma protein to hemoglobin ratio shows a narrow range (40 to 60 per cent) in experiments with visceral products.